2023
DOI: 10.1038/s41434-022-00381-y
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of FLT190, a liver-directed AAV gene therapy for Fabry disease

Abstract: Fabry disease is an X-linked lysosomal storage disorder caused by loss of alpha-galactosidase A (α-Gal A) activity and is characterized by progressive accumulation of glycosphingolipids in multiple cells and tissues. FLT190, an investigational gene therapy, is currently being evaluated in a Phase 1/2 clinical trial in patients with Fabry disease (NCT04040049). FLT190 consists of a potent, synthetic capsid (AAVS3) containing an expression cassette with a codon-optimized human GLA cDNA under the control of a liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In recent years, the safety and efficacy of AAV as a vector for gene therapy have been validated by clinical trials of AAV-mediated liver-targeted therapy for hemophilia A and B [ 36 38 ]; consequently, in vivo clinical applications of AAV-based vectors for liver-targeted gene therapy are rapidly increasing. Liver-targeted gene therapies for FD, namely FLT190 [ 39 ] and ST-920 [ 40 ], are both in phase 1/2 clinical research, and both have achieved good safety and efficacy. Therefore, we attempted to design a highly efficient AAV2/8-hGLA to establish a proof-of-concept for the clinical development of liver-targeted gene therapy for FD so as to improve the therapeutic effect and reduce the dose of AAV vector, thereby reducing the cost of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the safety and efficacy of AAV as a vector for gene therapy have been validated by clinical trials of AAV-mediated liver-targeted therapy for hemophilia A and B [ 36 38 ]; consequently, in vivo clinical applications of AAV-based vectors for liver-targeted gene therapy are rapidly increasing. Liver-targeted gene therapies for FD, namely FLT190 [ 39 ] and ST-920 [ 40 ], are both in phase 1/2 clinical research, and both have achieved good safety and efficacy. Therefore, we attempted to design a highly efficient AAV2/8-hGLA to establish a proof-of-concept for the clinical development of liver-targeted gene therapy for FD so as to improve the therapeutic effect and reduce the dose of AAV vector, thereby reducing the cost of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature show that as long as 5%–10% of α-Gal A enzyme activity remains, Gb3 and Lyso-Gb3 storage substrates can be effectively removed [ 41 ], indicating that the α-Gal A expressed in the AAV2/8-hGLA–treated FD mouse liver is effectively secreted into the plasma and taken up in FD mouse tissues, especially by the heart and kidney. Studies conducted earlier have shown that female FD mice exhibit reduced efficiency of transduction and transgene expression of AAV in comparison to males [ 25 , 32 , 39 ]. The effect may be caused by sex hormones, however, other studies pointed out that, unlike mice, androgens did not affect the transgene expression of AAV in nonhuman primates (NHPs) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal research using pseudo-typed AAV8 vectors to effectively transport FLT190 produced positive results, with -Gal A expression levels in NHPs equivalent to hGLA mRNA levels in the liver. Importantly, any FLT190-related toxicities or adverse effects were not observed, signifying preclinical potential of FLT190-directed gene therapy for treating Fabry disease 10 .…”
mentioning
confidence: 86%
“…Preclinical data on FLT190 showed safety and a steady rise in α-Gal A activity in mice and non-human primate models. [ 79 ] These results led to the Phase I/II MARVEL-1 study (NCT04040049). Untreated and previously treated adult male patients with classic FD were recruited.…”
Section: Treatmentmentioning
confidence: 99%